2010
DOI: 10.3746/jfn.2010.15.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Seed Oil Characteristics from Korean Ginseng, Chinese Ginseng (Panax ginseng C.A. Meyer) and American Ginseng (Panax quinquefolium L.)

Abstract: The chemical characteristics of seed oils of Asian ginseng (Panax ginseng C.A. Meyer) at different ages grown in Korea (3, 4 and 5-year old) and China (5-year old), and American ginseng (Panax quinquefoliu L., 5-year old) grown in China were compared. Total fatty acid composition showed a significantly higher oleic acid content in American (87.50%) than in Korean (68.02~69.14%) and Chinese ginseng seed oils (61.19%). At the sn-2 position, the highest oleic acid (81.09%) and lowest linoleic acid (15.77%) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…In contrast, studies on ginseng leaves, stems, or berries have mainly focused on skin cosmetics or antioxidant effects including the antioxidant and antiaging effects of ginseng berry extract [1], improvement of blood circulation [9], and prevention of skin aging [10]. Some studies have been reported regarding the ginseng seed itself, including saponin analysis of ginseng berries and seeds [2,11-13], free amino acid analysis [14], oil characteristics of ginseng species [15], and storage [16]. Studies on the phytosterol composition, content, and activity in American ginseng seeds have also been reported [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies on ginseng leaves, stems, or berries have mainly focused on skin cosmetics or antioxidant effects including the antioxidant and antiaging effects of ginseng berry extract [1], improvement of blood circulation [9], and prevention of skin aging [10]. Some studies have been reported regarding the ginseng seed itself, including saponin analysis of ginseng berries and seeds [2,11-13], free amino acid analysis [14], oil characteristics of ginseng species [15], and storage [16]. Studies on the phytosterol composition, content, and activity in American ginseng seeds have also been reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on Korean ginseng seeds are insufficient, particularly for the content, composition, and physiological activity of their phytosterols, which are known active ingredients in ginseng seeds [25]. Fatty acid composition and phytosterol content analysis of ginseng seed oil [17] and fatty acid analysis of ginseng seed oil [15] have been reported, but these studies were conducted on the phytosterol content analysis or oil analysis depending on the cultivation environment of the plants. Investigations have been lacking on the antioxidant and physiological activities of ginseng seed phytosterol.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer). We paid special attention to FA analysis, because, according to our data, the main FA in ginseng seeds is petroselinic 18:1(n-12) acid rather than the oleic one, as was reported earlier [3][4][5]7]. Petroselinic acid is known to have a specific biosynthesis pathway and a particular physiological activity [8,9].…”
mentioning
confidence: 65%
“…As is reported in some publications, ginseng seeds contain a substantial amount of oil (10-26 %) [2][3][4][5][6][7]. The major FAs of ginseng seeds are oleic 18:1(n-9), cis-vaccenic 18:1(n-7), and linoleic 18:2(n-6) [3][4][5]7]. The oleic acid content of oil from the American ginseng (Panax quinquefolius L.) reaches 87 % of total FA [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation